Immune response to surgical stress in spinal anaesthesia - Žura, Marijana (Array, 2009)
Surgical stress and anaesthesia cause immunosuppression that can predispose patients to postoperative infections and other complications. Anaesthesia may indirectly affect the immune system of surgical patients by modulating neurohormonal stress response. The aim of the study is to establish whether the examined cytokines either individually or in certain correlations may characterise regional (spinal) anaesthesia.Nine (9) patients with American Society of Anaesthesiologist status I or II who were scheduled for TURP (transurethral resection of the prostate) were anaesthetised in spinal anaesthesia.